Children first: women’s perspectives on evacuation at Fuego volcano and implications for disaster risk reduction - Bartel, Beth A.; Naismith, Ailsa K. (Frontiers in Earth Science, 2023)
As major drivers of behavior during crisis, cultural norms influence how disasters differentially affect people of different genders. Cultural gender norms also impact how authorities and at-risk populations approach disaster risk reduction strategies. At Fuego volcano, Guatemala, we applied qualitative methods to investigate women’s experiences of the evacuation process after a paroxysmal eruption on 7–8 March 2022. While participants’ experiences and decisions varied, we identified how gender influences evacuation dynamics within communities at Fuego volcano, including who evacuates and who decides at the community and household levels. We find that communities prioritized women for evacuation with the children and elderly in their care, yet prioritized men in the evacuation decision-making; that despite this hierarchy, a woman may override a male partner’s decision in order to prioritize the safety and well-being of her children; and that even if she overcomes social barriers to leaving, she may be unable to evacuate in a timely manner because of lack of transportation—a barrier impacting all residents, but especially women since they are the ones leading their households in evacuation. This gendered evacuation strategy disproportionately leaves men exposed to the threat, since most do not evacuate, and places the burden of evacuation on the women, who leave their homes and likely face the challenges of evacuation with multiple children in their care. This study contributes an example of how gendered norms impact disaster risk reduction strategy at an active volcano and how understanding gendered experiences of evacuation can inform future disaster risk reduction efforts.